Essays on beef cattle economics - McKendree, Melissa Gale Short (Kansas State University, 2017)
The U.S. beef industry is comprised of multiple, vertically connected segments. Beginning at the cow-calf level, cattle move through the industry to backgrounding/stocker operations, feedlots, and then to beef packers. The beef produced then continues to move through the marketing channel from beef packers to wholesalers and on to multiple final consumer outlets. Each level of the beef industry has both distinct and related economic issues. This dissertation contains three essays on beef cattle economics. Essay 1 focuses on price and animal health risk management at the feedlot level. Essays 2 and 3 explore how upstream demand changes impact primary beef suppliers. The objective of Essay 1 is to determine if feedlot operators manage price risk and animal health risk as two separate and independent risks or if they manage them jointly. The animal health attribute of interest is purchasing feeder steers from a single known source versus an auction with unknown background. The output price risk mitigation tools are futures contracts, forward contracts, other, and accept cash price at time of sale. Primary data is collected using an online survey administered to feedlot operators. Participants are placed in forward looking, decision making scenarios utilizing a split-sample block design. Evidence of a relationship between animal health risk and output price risk management is mixed. Ricardian rent theory (RRT) is tested in Essay 2 to determine if complete pass-through occurs from fed cattle and corn prices to feeder cattle prices. Monthly price data from December 1995 to December 2016 is used. Based on RRT, surplus rents should pass through the market to the holder of the scarcest resource. In cattle markets, feeder calves are the scarcest, widely traded resource and thus gains and losses at the feedlot theoretically pass-through to feeder cattle prices. The hypothesized pass-through rates suggested by RRT is calculated using monthly production data from the Focus on Feedlots data series. The regression pass-through estimates are tested against the hypothesized RRT pass-through. In many models, the estimated pass-through rate is statistically greater than the RRT hypothesized pass-through rate. Thus, when fed cattle or corn prices change, these changes are more than fully passed to cow-calf producers through the feeder cattle price. Evidence is found of asymmetric pass-through during times of herd expansion versus contraction. Essay 3 provides a quantification of how changes in retail and export beef demand are transmitted to different members of the beef industry. Understanding how information is transmitted from primary consumer demand through the supply chain is key for long-term prosperity of the U.S. cattle industry. However, empirical applications quantifying how demand signals are transmitted through vertically connected industries are limited. Using both naïve and forward looking price expectations, a four equation system of inverse demand and supply equations for live and feeder cattle is estimated. Using retail and export beef demand indices, the impacts of 1% change in retail or export demand on live cattle and feeder cattle prices are quantified.
Keywords: Beef cattle; Economics; Pass-through; Price transmission; Risk; Retail beef demand